Omental patch for lower uterine segment repair during caesarean section. Issue 4 (12th April 2022) - Carter, Edward; Le Bacq, Frank
Abstract : Increasing rates of caesarean section have contributed to a higher number of complications such as vesicouterine fistula. A G6P5 woman in her early forties presented for her third elective repeat caesarean section. At the time of delivery, there was uterine dehiscence and the fetus was visible through a large 7×5 cm transparent window in the lower segment. After delivery of the baby, the uterus was unable to be repaired with sutures so an omental patch was fixed on the lower segment to facilitate healing. It is hypothesised that the angiogenic properties of the omentum may have promoted healing of the uterine defect and reduced the risk of vesicouterine fistula by providing a protective barrier. The patient recovered well and by 4 months post partum, her menstrual cycle had returned. Thereby, the use of an omental patch during uterine repair may reduce long-term complications associated with repeat caesarean section.